Less than You Think. Young People's Belief in Online Misinformation - Pignard-Cheynel, Nathalie; Salerno, Sébastien (My University, 2022)
Our study provides an in-depth understanding of how young audiences (18-25 years old) are exposed to news and misinformation and how they attribute credibility to both types of content. It also advances journalistic practices in the fight against misinformation by producing digital formats and narratives with a visual focus adapted to young audiences. Our study covers six focus groups with 44 participants in four Swiss cantons and extended by 12 interviews conducted between 2019 and 2020. The participants were exposed to misinformation, fact-checking content produced by online news media, and original journalistic productions in line with the first results of the research and specially created by journalism students.
, SACM Annual Conference, Zürich
Keywords: Misinformation; disinformation; young people; news